Work Product Review Process Applied to Test Cases Review for Software Testing - Oliveira, Elisandra Souza De; Neves, Jhuan Magno Pisa; Cruz, André Figliuolo Da; Bezerra, Erick Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Testing is one of the most important factors in the software development cycle to obtain a quality product. It is essential to carry out effective tests to ensure that the software works as expected, meets all project requirements, and does not present defects after implementation. For this, the test cases must have a well-written and adequate structure, with actions and conditions that verify and cover all the functionalities and behaviors of the system. Even with several changes in requirements, business rules, new features, or adaptations that may occur during product development. This work describes an industrial case study where the work review process established by ISO/IEC 20246:2017 is implemented in the review of software test cases. As a result, a reduction in test execution time was achieved, as well as a reduction in the number of professionals involved as a result of better detection of defects during tests.